The Role of Effective Communication in Leadership: A Literature Review - Salsabila, Aisya Fajri; Febriantina, Susan; Danisworo, Herdina; Fauzia, Marcellia; Albana, Muhammad Ajib (Faculty of Economics and Business, Universitas Klabat, 2025)
Effective communication is crucial for leadership, particularly in the digital era. This study conducts a systematic literature review to examine key frameworks and empirical findings on leadership communication. It explores the adaptation of communication styles, the impact of digital transformation, and strategies for overcoming communication barriers. The findings indicate that effective communication enhances team performance, strengthens relationships, and aligns organizational goals. In digital and hybrid environments, leaders should leverage non-verbal cues and interactive technologies to improve engagement and productivity. Additionally, tailored communication training is essential for fostering adaptive leadership. This study offers valuable insights for designing leadership development programs and organizational communication strategies to address modern challenges and ensure long-term success.